The Similarities and Differences Between Chinese and Indonesia Culture - Yi Ying (Bina Nusantara University, 2014)
This paper aims to understand the similarities and differences between Chinese and Indonesia Culture. In order to achieve this goal, five culture aspect were analyzed. They are (1) greeting and farewell; (2) thanks and apologies; (3) honorifics and Qianci; (4) praise and politely refuse; (5) dinner and gifts. The research used comparative study method. By analyzing the five aspects of the Indonesia and Chinese culture, research concludes that the Chinese and Indonesian culture have similar common greetings and farewell, honorifics and low self-esteem, praise and politely refuse, dinner and gifts; and Chinese people have not left taboo.